Enhancing relationships between criminology and cybersecurity - Dupont, Benoît (Journal of criminology, 2021)
?Cybercrime? is an umbrella concept used by criminologists to refer to traditional crimes that are enhanced via the use of networked technologies (i.e. cyber-enabled crimes) and newer forms of crime that would not exist without networked technologies (i.e. cyber-dependent crimes). Cybersecurity is similarly a very broad concept and diverse field of practice. For computer scientists, the term ?cybersecurity? typically refers to policies, processes and practices undertaken to protect data, networks and systems from unauthorised access. Cybersecurity is used in subnational, national and transnational contexts to capture an increasingly diverse array of threats. Increasingly, cybercrimes are presented as threats to cybersecurity, which explains why national security institutions are gradually becoming involved in cybercrime control and prevention activities. This paper argues that the fields of cyber-criminology and cybersecurity, which are segregated at the moment, are in much need of greater engagement and cross-fertilisation. We draw on concepts of ?high? and ?low? policing (Brodeur, 2010) to suggest it would be useful to consider ?crime? and ?security? on the same continuum. This continuum has cybercrime at one end and cybersecurity at the other, with crime being more the domain of ?low? policing while security, as conceptualised in the context of specific cybersecurity projects, falls under the responsibility of ?high? policing institutions. This unifying approach helps us to explore the fuzzy relationship between cyber-crime and cyber-security and to call for more fruitful alliances between cybercrime and cybersecurity researchers.